2000
DOI: 10.1074/jbc.275.17.12438
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of the Heme Binding Module in Hemoglobin α- and β-Subunits

Abstract: In our previous work, we demonstrated that the replacement of the "heme binding module," a segment from F1 to G5 site, in myoglobin with that of hemoglobin ␣-subunit converted the heme proximal structure of myoglobin into the ␣-subunit type (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 66 publications
(63 reference statements)
0
10
1
Order By: Relevance
“…Our gelchromatography results of β 116HisfAsp chains like β 112CysfAsp chains also showed monomer formation predominated (5). The R chains are known to favor formation of monomers rather than tetramers, and NMR resonance signals of the heme region in these chains differ from those of β chains (14,26,29). This difference was thought to be mainly attributed to local structural differences between R and β chains (26).…”
Section: Discussionmentioning
confidence: 57%
“…Our gelchromatography results of β 116HisfAsp chains like β 112CysfAsp chains also showed monomer formation predominated (5). The R chains are known to favor formation of monomers rather than tetramers, and NMR resonance signals of the heme region in these chains differ from those of β chains (14,26,29). This difference was thought to be mainly attributed to local structural differences between R and β chains (26).…”
Section: Discussionmentioning
confidence: 57%
“…Once the methodology and its effectiveness have been established, other possible future work will be to change the size and number of blocks to be deleted or inserted in addition to changing the location where such mutations are introduced. This will be equivalent to a high‐throughput version of the previous efforts performed on nested deletion [17,18] or shuffling of proteins such as hemoglobin [19]. These works are useful not only from a molecular engineering viewpoint (such as creating minimum‐sized GFP) but also from a protein science viewpoint (such as exploring the protein sequence space).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, studies with bis-histidine Hbs have shown that the cyanide ligand displaces the His-E7 and not the His-F8 bond, which would indicate that the His-F8 bond is stronger than the His-E7 bond 51,52 . Finally, 1 HMR studies of rHbCN and heme-binding modules have shown that DCNh binds to His-F8 and not His-E7 5355 .…”
Section: Introductionmentioning
confidence: 97%
“…The affinity of heme for the His-F8 residue has been shown to be a major factor regulating association between the heme and globin chain . Additionally, mutated Hbs lacking the His-F8 residue were shown to exhibit much lower heme-binding affinity, faster heme loss, or the absence of heme. Furthermore, studies with bis-histidine Hbs have shown that the cyanide ligand displaces the His-E7 and not the His-F8 bond, which would indicate that the His-F8 bond is stronger than the His-E7 bond. , Finally, 1 H nuclear magnetic resonance studies of rHbCN and heme-binding modules have shown that DCNh binds to His-F8 and not His-E7. …”
mentioning
confidence: 99%